Stimulator of Interferon Genes (STING) Triggers Adipocyte Autophagy - Kornél Z. Varga; Katalin Gyurina; Ádám Radványi; Tibor Pál; László Sasi-Szabó; Haidong Yu; Enikő Felszeghy; Tamás Szabó; Tamás Röszer (Cells, 2023)
Innate immune signaling in adipocytes affects systemic metabolism. Cytosolic nucleic acid sensing has been recently shown to stimulate thermogenic adipocyte differentiation and protect from obesity; however, DNA efflux from adipocyte mitochondria is a potential proinflammatory signal that causes adipose tissue dysfunction and insulin resistance. Cytosolic DNA activates the stimulator of interferon response genes (STING), a key signal transducer which triggers type I interferon (IFN-I) expression; hence, STING activation is expected to induce IFN-I response and adipocyte dysfunction. However, we show herein that mouse adipocytes had a diminished IFN-I response to STING stimulation by 2′3′-cyclic-GMP-AMP (cGAMP). We also show that cGAMP triggered autophagy in murine and human adipocytes. In turn, STING inhibition reduced autophagosome number, compromised the mitochondrial network and caused inflammation and fat accumulation in adipocytes. STING hence stimulates a process that removes damaged mitochondria, thereby protecting adipocytes from an excessive IFN-I response to mitochondrial DNA efflux. In summary, STING appears to limit inflammation in adipocytes by promoting mitophagy under non-obesogenic conditions.